Evaluating the expression of heat shock protein 27 and topoisomerase II α in a retrospective cohort of patients diagnosed with locally advanced breast cancer and treated with neoadjuvant anthracycline-based chemotherapies - Zhuang, Yixuan; Zhang, Fan; Xu, Yue; He, Lifang; Huang, Wenhe; Hong, Chaoqun; Cui, Yukun (Frontiers in Oncology, 2023)
Background Neoadjuvant anthracycline-based chemotherapy (NAC) is a major regimen for the treatment of local advanced breast cancer (LABC), while resistance to NAC remains a paramount clinical obstacle. To investigate the role of heat shock protein 27 (Hsp27) and/or topoisomerase IIα (TopoIIα) in LABC patients treated with NAC, we performed this retrospective study. Methods Associations of Hsp27 transcripts with clinic-pathological characteristics, survival and drug response were investigated in public databases. Hsp27-related genes were identified, followed by functional enrichment analyses. Besides, two protein-protein interaction networks were built. Then, tumors from 103 patients who were diagnosed with LABC and received NAC were collected, and Hsp27 and TopoIIα were examined by Immunohistochemistry (IHC). Chi-square or Fisher’s exact tests were performed, as well as survival analyses. Results Either at the transcriptional level in public databases or at the protein level tested by IHC, a high level of Hsp27 was associated with aggressive tumor characteristics such as lymph node invasion and chemotherapy resistance. Hsp27-related genes mostly involved in the metabolic pathway and the gamete generation biological process. An elevated Hsp27 indicated a poor prognosis in patients with breast cancer (log-rank test P = 0.002 and 0.004 for disease-free survival [DFS] and overall survival [OS], respectively), while it might not be an independent predictor. Of note, tumors with high TopoIIα expression (TopoIIα+) was less likely to express Hsp27 (Hsp27+), in contrast to those with TopoIIα negativity (31.1% vs. 86.2%, P<0.001), and survival analyses revealed that patients with Hsp27+ and TopoIIα- tumors had a significantly lower DFS and OS (log-rank test P < 0.001 and 0.001, respectively), in contrast to the other three groups. Conclusions Hsp27 was associated with aggressive breast cancers and more predictable for the prognosis of LABC patients treated with NAC when concomitantly considering TopoIIα expression.